PENGARUH PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT DAN PUPUK NPK TERHADAP PERTUMBUHAN BIBIT TANAMAN GAHARU (Aquilaria malaccencis) - Nanda Satria; Wardati '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Agarwood plantis a commodity timber forest products that have high value and become a mainstay Indonesian export products. To support the process of cultivation of agarwood plant isrequired the provision of quality seeds and planting medium is supported by the availability of good and nutrient availability thar enough for the growth of seedlings. The research aim is to know the effect of the interaction of palm oil empty fruit bunch compost and NPK fertilizer and to get the best treatment for the growth of agartwood plant seedling. Theresearch was conducted at the experimental gardenAgricultural Faculty, University of Riau, Pekanbaru from May to September 2014. The research carried out experimentally using a completely randomized design (CRD) factorial consisting of two factors: palm oil empty fruit bunch compost and NPKfertilizer. The first factor is the dose of palm oil empty fruit bunch compost consists of 4 levels, that is: K0 (without palm oil empty fruit bunch compost), K1 (1/3 part of the media), K2 (1/2 part of the media), K3 (2/3 sections of the media). The second factor is the NPK fertilizer application consists of 4 levels: M0 (without NPK fertilizer), M1 (1 g/plant), M2 (2g/plant), M3 (3 g/plant). The results showed that the giving of palm oil empty fruit bunch compost and NPK fertilizer to agarwoor seedling gavethe best effect on fertilizer application of palm oil empty fruit bunch compost2/3 of the media with NPK 2 g/plants against accretion parameters plant height, stem diameter, number of leaves, stems and broad dry weight . Keyword: Agarwood seedling, palm oil empty fruit bunch compost, NPK fertilizer